VC and Cr3C2 doped WCoB-TiC ceramic composites prepared by hot-pressing. (November 2017) - Ke, Deqing; Pan, Yingjun; Xu, Yuanyuan; Wang, Pan; Wu, Run
Abstract: The grain growth inhibitors (GGIs) VC and Cr3 C2 doped WCoB-TiC ceramic composites were fabricated by hot-pressing. The microstructure, hardness, transverse rupture strength (TRS), fracture toughness (KIC ) and wear-resistance of WCoB-TiC ceramic composites were investigated. The results reveal that the grains can obviously become refined and the densification temperature of WCoB-TiC ceramic composites will be increased due to the VC and Cr3 C2 . The typical microstructure of WCoB-TiC ceramic composites mainly consist of bright W2 CoB2 grains, gray TiC particles, dark TiB2 and pores. WCoB-TiC ceramic composites doped with 0.3 wt% VC and 0.3 wt% Cr3 C2 hot-pressing at 1420 °C show the optimum mechanical properties (hardness, TRS and KIC are 92.6 HRA, 1976 MPa and 14.8 MPa m 1/2, respectively) and the best dry sliding wear-resistance. Highlights: The grains can obviously become refined and the densification temperature of WCoB-TiC ceramic composites will be increased due to the VC and Cr3 C2 . The typical microstructure of WCoB-TiC ceramic composites mainly consist of bright W2 CoB2 grains, gray TiC particles, dark TiB2 and pores. WCoB-TiC ceramic composites doped with 0.3 wt.% VC and 0.3 wt.% Cr3 C2 hot-pressing at 1420 °C show the optimum mechanical properties and the best dry sliding wear resistance.